Social networks and health-related quality of life: a population based study among older adults Redes sociales y calidad de vida relacionada a la salud: un estudio de base poblacional en adultos mayores - Katia Gallegos-Carrillo; Jyoti Mudgal; Sergio Sánchez-García; Fernando A Wagner; Joseph J Gallo; Jorge Salmerón; Carmen García-Peña (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To examine the relationship between components of social networks and health-related quality of life (HRQL) in older adults with and without depressive symptoms. MATERIAL AND METHODS: Comparative cross-sectional study with data from the cohort study "Integral Study of Depression", carried out in Mexico City during 2004. The sample was selected through a multi-stage probability design. HRQL was measured with the SF-36. Geriatric Depression Scale (GDS) and the Short Anxiety Screening Test (SAST) determined depressive symptoms and anxiety. T-test and multiple linear regressions were conducted. RESULTS: Older adults with depressive symptoms had the lowest scores in all HRQL scales. A larger network of close relatives and friends was associated with better HRQL on several scales. Living alone did not significantly affect HRQL level, in either the study or comparison group. CONCLUSIONS: A positive association between some components of social networks and good HRQL exists even in older adults with depressive symptoms. OBJETIVO: Examinar la relación entre componentes de redes sociales y calidad de vida relacionada con la salud (CVRS) de adultos mayores con o sin síntomas depresivos. MATERIAL Y MÉTODOS: Estudio transversal comparativo con datos de la cohorte "Estudio Integral de Depresión", realizado en la Ciudad de México en 2004. La muestra fue seleccionada por diseño probabilístico multietápico. La CVRS se midió con SF-36, mientras que Geriatric Depression Scale y Short Anxiety Screening Test determinaron síntomas de depresión y ansiedad. El análisis consistió de prueba T y regresiones lineales múltiples. RESULTADOS: Ancianos con síntomas de depresión reportaron puntuaciones más bajas en todas las escalas de CVRS; una red más grande de familiares y amigos se asoció con mejor CVRS en varias escalas. Vivir solo no afectó la CVRS en grupos de estudio y comparación. CONCLUSIONES: Existe una asociación positiva de algunos componentes de las redes sociales con la CVRS, incluso en ancianos con síntomas depresivos.